Epistemology : contemporary readings - Huemer, Michael (Routledge, 2002)
This comprehensive anthology draws together classic and contemporary readings by leading philosophers on epistemology. Ideal for any philosophy student, it will prove essential reading for epistemology courses, and is designed to complement Robert Audi's textbook Epistemology: A Contemporary Introduction (Routledge, 1998). Themes covered include, perception, memory, inductive inference, reason and the a priori, the architecture of knowledge, skepticism, the analysis of knowledge, testimony. Each section begins with an introductory essay, guiding students into the topic. Includes articles by: Russell, Hume, Berkeley, Malcolm, Quine, Carnap, J.L. Austin, Pollock, Nozick, Putnam, G.E. Moore, Huemer, Reid, Plato, BonJour, Coady, Carroll, Fumerton, Edwards, Foster, Howson, Urbach, Stove, Empiricus, Oakley, Alston, Gettier, Clark, Goldman, Lehrer, Paxson, DeRose, Dretske, Klein and Chisholm